Optimal trough concentration of voriconazole with therapeutic drug monitoring in children: A systematic review and meta-analysis. Issue 2 (February 2021) - Hanai, Yuki; Hamada, Yukihiro; Kimura, Toshimi; Matsumoto, Kazuaki; Takahashi, Yoshiko; Fujii, Satoshi; Nishizawa, Kenji; Takesue, Yoshio
Abstract: Objectives: This systematic review and meta-analysis was designed to determine the optimal trough concentration of voriconazole for children with invasive fungal infections (IFIs). Methods: We searched electronic databases (PubMed, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov and Japana Centra Revuo Medicina) for clinical studies describing the voriconazole trough concentration. We used stepwise cut-off values of 1.0–2.0 mg/L for efficacy and 3.0–6.0 mg/L for safety. The efficacy outcomes were treatment success and all-cause mortality, and the safety outcomes were hepatotoxicity, neurotoxicity and all-cause adverse events. Results: Nine studies involving 211 patients were included in the analysis. The probability of treatment success against IFIs was significantly increased at cut-off values of ≥1.0 mg/L (odds ratio [OR] = 2.65, 95% confidence interval [CI] = 1.20–5.87). Our analysis did not find any relationship between the trough concentration and survival. Concerning safety, the occurrence of any outcomes did not significantly differ according to the voriconazole trough concentrations at any cut-off value. However, in a subgroup analysis of Asian study locations, a significantly higher risk of hepatotoxicity was demonstrated at voriconazole trough cut-off values ≥ 3.0 mg/L (OR = 8.40, 95% CI = 1.36–51.92). Although a significant correlation between the voriconazole concentration and hepatotoxicity was evident in regression curve analysis, (y = 0.1198e 0.2298x ), no correlation was demonstrated for neurotoxicity (y = 0.3913e −0.008x ). Conclusion: Our findings suggest that the optimal trough concentration for increasing clinical success and minimizing hepatotoxicity during voriconazole therapy in children with IFIs, particularly for Asian populations, is 1.0–3.0 mg/L.